Journal of neuroeducation = revista de neuroeducación = revista de neuroeducació - Universidad de Barcelona (Universitat de Barcelona, 2020)
"Neuroeducation as an academic discipline arises from the intersection between the fields of knowledge of neuroscience, cognitive psychology and education, and their other related disciplines"--About, viewed April 11, 2023.
Keywords: Neurosciences : Periodicals; Cognitive psychology : Periodicals; Education : Periodicals